Reconstructing Biblical Authority in Christian Religious Education Amid Global Cultural Fragmentation - Talizaro Tafonao; Desy Mintin; Daniel Agustin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The development of globalization and digital culture has given rise to an epistemological crisis that shifts the authority of truth from revelation to social construction, so that the authority of the Bible in Christian education is increasingly marginalized. This condition has an impact on the low internalization of the value of faith, where students understand the Bible cognitively but do not live it in daily practice. This research aims to reconstruct the authority of the Bible in Christian education through an integrative and contextual approach in the midst of global cultural fragmentation. This research uses a qualitative approach with a library research method that integrates theological, pedagogical, and digital cultural contexts. Data were obtained from theological literature, educational theory, and relevant journal articles, which were analyzed using content analysis techniques and theological-constructive reflection. The results show that the crisis of biblical authority is influenced by epistemic shifts, the dominance of post-truth culture, low internalization of values, and non-contextual pedagogical approaches. This research creates a model of reconstruction of biblical authority that integrates the epistemological, pedagogical, and bruxistic dimensions in a transformational manner. In conclusion, this reconstruction does not change the theological substance of the Bible but updates the approach to learning to be more dialogical, reflective, and contextual, so that the authority of the Bible remains relevant in shaping the faith and character of learners in the global era.